Comparison of Proteome Composition of Serum Enriched in Extracellular Vesicles Isolated from Polycythemia Vera Patients and Healthy Controls - Anna Fel; Aleksandra E. Lewandowska; Petro E. Petrides; Jacek R. Wiśniewski (Proteomes, 2019)
Extracellular vesicles (EVs), e.g., exosomes and microvesicles, are one of the main networks of intercellular communication. In myeloproliferative neoplasms, such as polycythemia vera (PV), excess of EVs originating from overabundant blood cells can directly contribute to thrombosis through their procoagulant activity. However, the proteomic composition of these vesicles in PV patients has not been investigated before. In this work, we examined the proteomic composition of serum EVs of PV patients in comparison to healthy controls. We processed EV-enriched serum samples using the Multiple Enzyme Filter Aided Sample Preparation approach (MED-FASP), conducted LC-MS/MS measurements on a Q-Exactive HF-X mass spectrometer, and quantitatively analyzed the absolute concentrations of identified proteins by the Total Protein Approach (TPA). Thirty-eight proteins were present at statistically significant different concentrations between PV patients’ study group and healthy controls’ group. The main protein components deregulated in PV were primarily related to excessive amounts of cells, increased platelet activation, elevated immune and inflammatory response, and high concentrations of procoagulant and angiogenic agents. Our study provides the first quantitative analysis of the serum EVs’ proteome in PV patients. This new knowledge may contribute to a better understanding of the secondary systemic effects of PV disease and further development of diagnostic or therapeutic procedures.